SERMONS BY THE AUTHOR OF THE THEOGNOSIA, ATTRIBUTED TO GREGORY OF NYSSA - Bell, H. I. (The journal of theological studies, 1925)
H. I. BELL; SERMONS BY THE AUTHOR OF THE THEOGNOSIA, ATTRIBUTED TO GREGORY OF NYSSA, The Journal of Theological Studies, Volume os-XXVI, Issue 104, 1 July 1925,